Control by state observer of PEMFC anodic purges in dead-end operating mode. Issue 15 (2015) - Piffard, Maxime; Gerard, Mathias; Bideaux, Eric; Fonseca, Ramon Da; Massioni, Paolo
Abstract: A Proton Exchange Membrane Fuel Cell (PEMFC) needs an active system to control all the ancillaries and ensure optimal operating conditions, especially in a fuel cell vehicle. For the fuel cell system architecture, dead-end anode is the cheapest architecture for the hydrogen line and also the one that leads to important reversible and irreversible degradations if not appropriately managed. To address the cost and durability issues on fuel cell vehicles, this study proposes a state observer which aims at estimating online the nitrogen saturation in the anode side in order to trigger the purge at a given criterion. This observer is based on a simple set of equations extracted from a detailed 2D-meshed model. Nitrogen buildup is evaluated in simulation with different road profiles with less than 5% error. Moreover the fuel cell system efficiency increases compared to the other existing purge strategies, so as the mileage. The observer can also be used to develop other optimal strategies to minimize the irreversible degradations of the fuel cell.